(untitled) (Orfeu, 2020)
In the field of studying the children’s repertoire, under a historical and theoretical musical perspective, the objective of this article is to shed light on the Brazilian context, to enunciate pertinent foundations to what are works for, by and with children. This research work is qualitative, applied and exploratory, and its predominant procedure is a case study, including bibliographic review, textual and musical analysis. The piece O Navio Pirata (CARDOSO, 1981), whose contextualization and analysis were conducted by the CDG Analysis Model (NUNES, 2012), is here considered the most representative of the subject investigated, among those published in the collection Música Brasileira para Coro Infantil, from Funarte (BRASIL, 1979). The results showed open theoretical-musical components and expressive indications of performative character, which are underlying, inspiring, transgressive and susceptible to expansion, by the interpreters. In conclusion, children’s musical pieces need to foresee and welcome kaleidoscopic co-authorship, by children, in their scores.